Дослідження властивостей керамічних матеріалів для харчової промисловості - Литвиненко, Олександр Анатолійович; Пащенко, Богдан Сергійович; Штефан, Євгеній Васильович (My University, 2020)
У статті наведено результати досліджень зносостійкості технічної кераміки для деталей і вузлів обладнання харчової промисловості. На основі математичного моделювання деформації керамічних матеріалів показано, що на їх зносостійкість впливає схема деформації, мікроструктура, пластичність та ударна в’язкість. Це дає змогу отримувати практично непористий матеріал з раціональною орієнтацією зерен і текстурою деформацій. З урахуванням результатів моделювання проведені дослідження порівняльної зносостійкості технічної кераміки різних типів. Показано, що зношування керамічних матеріалів є складним процесом руйнування їх окремих складових з подальшою втратою маси. Встановлено, що найбільш ефективним напрямком підвищення зносостійкості керамічних матеріалів є збільшення вмісту оксиду алюмінію. Дослідження з використанням чисельних методів задовільно узгоджуються з результатами фізичних експериментів.

The results of the technical ceramics wear resistance for parts and units of food industry equipment are presented in article. Preliminary research shows that ceramic materials are not inferior to metals in terms of wear resistance. The material mathematical model is based on the two-phase disperse system consideration with a gas dispersive medium. This would suggest that there is no phase relative movement. So, the phase separation is neglected and dispersed medium characteristics averaging may be proposed. Such method led to substantial simplification of mathematical design procedure. The different types of technical ceramics comparative wear resistance researching were carried out with the simulation results accounting. It is shown that the ceramic materials wear is a complex process of their individual components destruction with the subsequent mass loss. The dependence of the specimen weight losses rate upon the forced vibrations frequency and the base component content is estimated by the method of experiment mathematical planning with subsequent experimental verification. In this case, a cyclical nature of destruction is observed. It includes the accumulation of defects, the development of cracks and the wearing products formation. This is preceded by the microcracks accumulation, which is determined by the material grain size. Most obviously is implemented grain boundary fracture mechanism in small dispersed single-phase oxide ceramics and in more coarsely dispersed macrocracks pass through the grain body. Determined that the predominant direction of the ceramic materials wear resistance increasing is the aluminum oxide content increasing. The most wear resistant and durable is corundum ceramics with an aluminum oxide content of more than 90%. At the same time, the action of mechanical intensity on wearing does not significantly affect. Shown, that the research with numerical methods using are in satisfactory agreement with the results of physical experiments.
Keywords: обладнання; зносостійкість; технічна кераміка; оксид алюмінію; ультразвукова кавітація; equipment; wear resistance; technical ceramics; aluminum oxide; ultrasonic cavitation; кафедра машин і апаратів харчових та фармацевтичних виробництв; кафедра експертизи харчових продуктів